Thermal barrier coating resistant to marine salt spray corrosion and preparation method of thermal barrier coating

By adopting a multi-layer ceramic coating structure on the hot end components of marine gas engines, combined with laser cladding and electrophoretic deposition technology, a dense SiC fiber-reinforced YSZ coating is formed, which solves the durability of marine salt spray corrosion on YSZ coatings. , achieving higher corrosion resistance and thermal shock resistance.

CN119194440APending Publication Date: 2024-12-27SANYA SCI & EDUCATION INNOVATION PARK WUHAN UNIV OF TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411231972.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The thermal end components of marine gas engines face the dual attack of high temperatures and complex corrosion in the marine environment. The existing YSZ thermal barrier coating is prone to cracks and failures in long-term use, making it difficult to meet the strict requirements of marine salt spray corrosion.

Method used

Using a multi-layer ceramic coating structure, including a substrate, an adhesive layer and a ceramic mesh layer. The ceramic mesh layer consists of a transition ceramic layer and a fiber toughening layer. The layered structure is formed by laser cladding and electrophoretic deposition. Rare earth element-doped NiAl alloy and doped YSZ material, SiC fiber-reinforced YSZ layer, form a dense composite coating.

Benefits of technology

It significantly improves the corrosion resistance, thermal shock and thermal insulation properties of the coating, extends its service life, and effectively prevents crack diffusion and corrosive seepage through the design of the fiber toughening layer, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194440A_ABST
    Figure CN119194440A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of thermal barrier coatings, in particular to a marine salt spray corrosion resistant thermal barrier coating and a preparation method thereof. The thermal barrier coating comprises a base body, a bonding layer and a ceramic embedding layer which are sequentially arranged from bottom to top. The ceramic embedded layer comprises a transition ceramic layer and a fiber toughening layer; a plurality of grooves are uniformly formed in one side surface, far away from the bonding layer, of the transition ceramic layer; protrusions in one-to-one correspondence with the grooves are arranged on the side face, making contact with the transition ceramic layer, of the fiber toughening layer, and the transition ceramic layer and the fiber toughening layer are matched and compounded into a layered structure through the grooves and the protrusions. Through a multi-layer composite structure and an interlayer embedded structure, the composite material has good corrosion resistance, thermal shock resistance and heat insulation performance, and the preparation process is simple, easy to implement and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal barrier coatings, and in particular to a thermal barrier coating resistant to marine salt spray corrosion and a preparation method thereof. Background Art

[0002] With the comprehensive expansion of overseas transportation business and the continuous advancement of military modernization, extremely high requirements are placed on the research and development and manufacturing technology of my country's shipbuilding industry. The hot end components of marine gas turbines, such as combustion chambers, blades, and turbine impellers, need to face the coupled impact of high temperature, high-speed gas, and marine multi-component corrosive media for a long time. The service conditions of the components have reached or partially exceeded the service limits of their own materials, which greatly affects the service life of the components and the performance of the gas turbine. It is necessary to prepare a thermal barrier protective coating on its surface to ensure its long-term service stability under harsh conditions.

[0003] At present, the initial design conditions of YSZ and its derived thermal barrier coating systems are mostly for the service environment of the hot end components of aircraft engines, and their designed service conditions are obviously different from the service environment of the hot end components of marine gas engines. Compared with aircraft engines, marine gas engine thermal barrier coatings not only need to face a longer service cycle, but also the marine environmental corrosive substances are more complex and have higher corrosion intensity. The penetration of marine high-temperature corrosive substances is more likely to cause cracks to expand inside the coating and even fail. The YSZ ceramic surface layer has high rigidity and weak plastic toughness, which makes it easy for cracks in the ceramic surface layer to expand inside the ceramic layer, eventually causing the surface layer to fracture and fail, reducing the thermal cycle life of the thermal barrier coating, so it is necessary to put forward higher requirements for the thermal barrier coating of the hot end components serving in the ocean.

[0004] In order to solve the above problems, the mechanical properties of ceramic materials are improved by doping fibrous toughening phases with good mechanical properties and a certain aspect ratio inside the ceramic materials, and a multi-layer ceramic layer structure is used, which has been proven to be an effective way to increase the service life of thermal barrier coatings. However, during long-term high-temperature service, thermal barrier coatings with multi-layer composite structures made of different materials are prone to interlayer delamination failure due to differences in the mechanical properties of the materials. Although the corrosion resistance is improved, the service life is greatly shortened.

[0005] Therefore, in order to meet the needs of hot end components serving in complex marine corrosive environments, the present application proposes a thermal barrier coating resistant to marine salt spray corrosion and a preparation method thereof. Summary of the invention

[0006] In order to make up for the deficiencies of the prior art and solve the technical problems existing in the background technology, the present invention proposes a thermal barrier coating resistant to marine salt spray corrosion and a preparation method thereof.

[0007] The present invention is achieved through the following technical solutions:

[0008] A thermal barrier coating resistant to marine salt spray corrosion, comprising: a substrate, a bonding layer and a ceramic interlayer;

[0009] The substrate, bonding layer and ceramic embedding layer are arranged in sequence from bottom to top;

[0010] The ceramic mosaic layer includes a transition ceramic layer and a fiber toughening layer; a plurality of grooves are evenly arranged on a side of the transition ceramic layer away from the bonding layer; protrusions corresponding to the grooves are arranged on a side of the fiber toughening layer in contact with the transition ceramic layer, and the transition ceramic layer and the fiber toughening layer are compounded into a layered structure through the grooves and the protrusions.

[0011] Preferably, the particle sizes in the bonding layer, transition ceramic layer and fiber toughening layer are divided into three grades, wherein:

[0012] The bonding layer is a large particle material with a particle diameter of 300-1000nm;

[0013] The transition ceramic layer is a micron-sized particle material, and the particle diameter is 200-300nm;

[0014] The fiber toughening layer is a nano-scale particle material, and the particle diameter is 1-10nm.

[0015] Preferably, the particle size of the bonding layer is controlled by the particle size of the pore former and the bonding layer material, wherein:

[0016] The pore-forming agent includes one of polyester powder, polystyrene powder or high-density polyethylene powder.

[0017] Preferably, the protrusion is a hemispherical protrusion with a sawtooth-shaped cross section, and the diameter of the protrusion structure is 10-40 μm.

[0018] Preferably, the base material of the base body is a high-temperature nickel-based alloy; the bonding layer material of the bonding layer is a modified NiAl alloy doped with 0.05 at % Hf element.

[0019] Preferably, the transition ceramic layer material in the transition ceramic layer is modified YSZ doped with 0.05at%-0.1at% Dy; the toughening layer material in the fiber toughening layer is YSZ doped with SiC fiber, and the mass proportion of SiC fiber in the fiber toughening layer composite material is 10%-30%.

[0020] A method for preparing the thermal barrier coating suitable for the above-mentioned marine salt spray corrosion resistance comprises the following steps:

[0021] Step S1: After preheating the substrate, the bonding layer material is sprayed onto the surface of the substrate using a spray gun by laser cladding method to obtain a bonding layer with a thickness of 100-150 μm;

[0022] Step S2: Based on step S1, preheat it again, and immediately deposit a transition ceramic layer on the surface of the bonding layer by laser cladding to obtain a transition ceramic layer with a bonding layer thickness of 200-300 μm;

[0023] Step S3: Based on step S2, further preheating is performed, and a fiber toughening layer is immediately deposited by electrophoretic deposition to obtain a fiber toughening layer with a thickness of 100-200 μm.

[0024] Preferably, the preheating temperature in steps S1 and S3 is 280-300° C., and the preheating time is 15-30 min; the preheating temperature in step S2 is 800-850° C., and the preheating time is 15-20 min.

[0025] Preferably, in step S3, when using electrophoretic deposition, the high-temperature nickel-based alloy of the substrate is used as the positive electrode, and graphite is used as the negative electrode and placed in the suspension, the electrode spacing is 20-100 mm, the deposition voltage is 20-40 V, the deposition time is 2-10 min, and the post-deposition heat treatment temperature is 80-120 ° C, and the heat treatment time is 4-10 h.

[0026] Preferably, at the rear end of the laser cladding spraying in step S2, the spraying device is changed so that the micron particles on the top of the transition ceramic layer are accumulated to present a groove matching the protrusion.

[0027] The beneficial effects of the present invention are:

[0028] 1. The multilayer composite structure and interlayer interlocking structure of the thermal barrier coating of the present invention have good corrosion resistance, thermal shock resistance and heat insulation performance, and the preparation process is simple, easy to implement, and suitable for large-scale production.

[0029] 2. The bonding layer material in the present invention uses a doped alloy of rare earth element Hf and modified NiAl, and the ceramic layer material is YSZ doped with Dy element. The rare earth element doped YSZ coating has better molten salt thermal corrosion resistance and phase stability. The top is a toughening layer of SiC fiber / YSZ composite material. The fibrous tough phase in the coating matrix will consume a lot of energy to form a new surface when debonding, pulling out and breaking, and generate additional strain energy and a large amount of fracture energy. While preventing the penetration of molten corrosive products, it also effectively limits the growth and diffusion of cracks generated at alternating temperatures during thermal cycling in the coating.

[0030] 3. The fiber toughening layer sprayed by the electrophoretic deposition method and the ceramic transition layer and bonding layer sprayed by the laser cladding method in the present invention can densify the coating surface, eliminate the layered structure, pores and oxide inclusions of the coating, form a uniform and dense ceramic coating, prevent the invasion of corrosive substances, and improve the high-temperature corrosion resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a schematic diagram of the structure of the thermal barrier coating in the present invention;

[0032] Figure 2 is a flow chart of the method for thermal barrier coating in the present invention;

[0033] Figure 3 Schematic diagram of the interlayer bridging effect of SiC fiber and the prevention of crack propagation

[0034] Figure 4 This is a comparison chart of the heat insulation effect of the present invention and the comparative example (unit: ℃)

[0035] Figure 5 This is an equivalent stress comparison diagram of the present invention (unit: MP).

[0036] In the figure:

[0037] 1. substrate; 2. bonding layer; 3. ceramic interlocking layer; 301. transition ceramic layer; 302. fiber toughening layer. DETAILED DESCRIPTION

[0038] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0039] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. The present invention is further described according to the accompanying drawings and specific embodiments of the present invention, and the preferred implementation methods and materials described in the present invention are only for demonstration purposes.

[0040] A thermal barrier coating resistant to marine salt spray corrosion, such as Figure 1 As shown, it includes: a substrate 1, a bonding layer 2 and a ceramic embedding layer 3;

[0041] The substrate 1, the bonding layer 2 and the ceramic embedding layer 3 are arranged in sequence from bottom to top;

[0042] The ceramic interlocking layer 3 includes a transition ceramic layer 301 and a fiber toughening layer 302; a plurality of grooves are evenly arranged on the side of the transition ceramic layer 301 away from the bonding layer 2; protrusions corresponding to the grooves are arranged on the side of the fiber toughening layer 302 in contact with the transition ceramic layer 301, and the transition ceramic layer 301 and the fiber toughening layer 302 are compounded into a layered structure through the grooves and the protrusions.

[0043] The particle sizes in the bonding layer 2, transition ceramic layer 301 and fiber toughening layer 302 are divided into three levels, wherein:

[0044] The bonding layer 2 is a large particle material with a particle diameter of 300-1000nm;

[0045] The transition ceramic layer 301 is a micron-sized particle material, and the particle diameter is 200-300nm;

[0046] The fiber toughening layer 302 is a nano-scale particle material, and the particle diameter is 1-10 nm.

[0047] The present invention selects three levels of particle size through the bonding layer 2, the transition ceramic layer 301 in the ceramic interlocking layer 3 and the fiber toughening layer 302, thereby forming three levels of particles, which is conducive to the filling of the micro-agglomerate particles of the upper layer to be more consistent. And the ceramic interlocking layer 3 arranged on the surface of the bonding layer 2 is a dense particle.

[0048] The particle size of the bonding layer 2 is controlled by the particle size of the pore former and the bonding layer material, wherein:

[0049] The pore-forming agent includes one of polyester powder, polystyrene powder or high-density polyethylene powder.

[0050] Specifically choose polyester powder.

[0051] The protrusions are hemispherical protrusions with a sawtooth-shaped cross section, and the diameter of the protrusion structure is 10-40 μm.

[0052] The base material of the base body 1 is a high-temperature nickel-based alloy; the bonding layer material of the bonding layer 2 is a modified NiAl alloy doped with 0.05 at% Hf element.

[0053] The transition ceramic layer material in the transition ceramic layer 301 is modified YSZ doped with 0.05at%-0.1at% Dy; the toughening layer material in the fiber toughening layer 302 is YSZ doped with SiC fibers, and the mass proportion of SiC fibers in the fiber toughening layer composite material is 10%-30%.

[0054] Embodiment 1:

[0055] For surface treatment of nickel-based alloy blades for marine gas turbines, nitric acid etching cleaning fluid is used for chemical cleaning, usually with a ratio of nitric acid (HNO3, concentration of 65-70%) to water of 1:1. Ensure that grease, dirt and oxides are removed to obtain a surface roughness of Ra <5.

[0056] A method for preparing a thermal barrier coating resistant to marine salt spray corrosion, such as Figure 2 As shown, the following steps are included:

[0057] Step S1 , forming an adhesive layer 2 on a substrate 1 .

[0058] Adding the rare earth element Hf to the NiAl eutectic alloy can significantly refine the alloy structure and grains, effectively improve the room temperature and high temperature tensile plasticity and strength of the NiAl eutectic alloy, and improve its oxidation resistance; however, excessive rare earth elements reduce the mechanical properties and oxidation resistance of the alloy.

[0059] Therefore, in the embodiment of the present invention, the material ratio of the bonding layer 2 is as follows:

[0060] 0.05 at. % Hf is added to each NiAl eutectic alloy containing 50 at. % Ni and 50 at. % Al, and the mixture is mixed by mechanical mixing to obtain a mixed powder.

[0061] After the substrate 1 is preheated, the bonding layer material is sprayed onto the surface of the substrate 1 using a spray gun. The preheating temperature is 300° C. and the preheating time is 30 minutes.

[0062] In the embodiment of the present invention, the spraying method used is laser cladding method, the defocusing amount is 40-50mm, the spot diameter acting on the workpiece after defocusing is 5mm, the laser power is 3KW, the scanning speed is 5mm / s, the argon protection flow rate is 45L / min, and the obtained bonding layer thickness is 150μm.

[0063] Step S2, forming a transition ceramic layer 301 on the surface of the bonding layer 2.

[0064] Specifically, 0.05 at % Dy is added to a YSZ material having a ratio of 80 mol % ZrO 2 and 20 mol % Y 2 O 3 by a mechanical powder mixing method to obtain a mixed powder.

[0065] After preheating, the substrate 1 and the bonding layer 2 are immediately deposited with a transition ceramic layer 301 on the surface of the bonding layer 2 by laser cladding. The preheating temperature is 800°C, the preheating time is 20 minutes, and the laser cladding device is set with a defocusing amount of 40-50 mm, a spot diameter of 5 mm acting on the workpiece after defocusing, a laser power of 3 KW, a scanning speed of 5 mm / s, and an argon protection flow rate of 45 L / min. The thickness of the obtained transition ceramic layer 301 is 250 μm.

[0066] Step S3 , forming a fiber toughening layer 302 on the surface of the transition ceramic layer 301 .

[0067] Specifically, in the ceramic layer material 8YSZ (6-8wt.% yttria-stabilized zirconia), the YSZ powder is refined by adding a polyethylene dispersant with a mass fraction of 2-6%, and SiC fiber powder is added. The powders are evenly mixed by mechanical mixing to obtain SiC fiber / YSZ mixed powder, in which the mass proportion of SiC fiber is 20%.

[0068] After preheating the substrate 1, the bonding layer 2 and the transition ceramic layer 301, the fiber toughening layer 302 is immediately deposited by electrophoretic deposition, and the SiC fiber / YSZ mixed powder, acetylacetone solvent, Al2O3 powder, dispersant solution and deionized water are mixed and stirred to prepare a suspension;

[0069] The concentration of the dispersant solution is 0.2wt%, and a small amount of iodine is added. The preheating temperature is 300℃, the preheating time is 30min, and the high-temperature nickel-based alloy is used as the positive electrode and graphite is used as the negative electrode in the suspension. The electrode spacing is 80mm, the deposition voltage is 40V, and the deposition time is 10min; the post-deposition heat treatment temperature is 100℃, and the heat treatment time is 8h. The obtained fiber toughening layer has a thickness of 100μm.

[0070] Furthermore, in steps S1 and S2, the bonding layer 2 and the transition ceramic layer 301 are formed on the substrate 1 by laser cladding. The laser cladding method of the present invention is a method in the prior art, and the coating has high compactness, and the obtained coating has high corrosion resistance and thermal shock resistance.

[0071] Furthermore, in step S3, the method of forming the fiber toughening layer on the surface of the transition ceramic layer 301 is electrophoretic deposition. The electrophoretic deposition method can better prepare the ceramic top layer of the SiC fiber / YSZ composite material, and the prepared fiber toughening layer is more closely combined with the transition ceramic layer 301 after high-temperature calcination.

[0072] Furthermore, at the rear end of the laser cladding spraying in step S2, the spraying device is changed so that the micron particles accumulated on the top of the transition ceramic layer 301 present a groove matching the protrusion.

[0073] Comparative Example 1:

[0074] The only difference from Example 1 is that the top fiber toughening layer is removed, the thickness of the transition ceramic layer 301 is 350 μm, and the other steps and conditions are the same as those in Example 1.

[0075] Comparative Example 2:

[0076] The only difference from Example 1 is that the interlayer interlocking structure of the composite ceramic layer is removed, and the other steps and conditions are the same as those of Example 1.

[0077] Comparative Example 3:

[0078] The only difference from Example 1 is that the intermediate transition ceramic layer 301 is removed, the thickness of the fiber toughening layer is 350 μm, and the other steps and conditions are the same as those in Example 1.

[0079] Table 1 lists the performance test results of Example 1 and Comparative Examples 1-3. The thermal cycle performance test was performed on the coated samples using a thermal shock furnace. The highest test temperature was 1200°C, and the cycle period was 5 minutes of heating and 1 minute of water cooling. The diffusion depth of the corrosive product after 10 cycles was observed by electron microscope images, and the surface temperature of the substrate under a temperature load of 1200°C was observed by computer finite element analysis software. The specific results are shown in Table 1. From the data results in Table 1, it can be seen that compared with the thermal barrier coating without a fiber toughening layer, the composite coating of the fiber toughening layer + ceramic transition layer has better corrosion resistance; compared with the thermal barrier coating without a mosaic structure, the coating with a hemispherical protrusion mosaic structure between layers has better thermal shock resistance.

[0080]

[0081] The specific effects are as follows:

[0082] The bonding layer material is a doped alloy of rare earth element Hf and modified NiAl, and the ceramic layer material is YSZ doped with Dy element. The rare earth element doped YSZ coating has better phase stability in resistance to molten salt hot corrosion.

[0083] The top is a toughening layer of SiC fiber / YSZ composite material. The fibrous tough phase in the coating matrix will consume a lot of energy to form a new surface when debonding, pull-out and fracture occur, and will generate additional strain energy and a large amount of fracture energy.

[0084] While preventing the penetration of molten corrosion products, it also effectively limits the growth and spread of cracks in the coating caused by the alternating temperatures during thermal cycling.

[0085] In addition, the fiber toughening layer sprayed by electrophoretic deposition and the ceramic transition layer and bonding layer sprayed by laser cladding can densify the coating surface, eliminate the layered structure, pores and oxide inclusions of the coating, form a uniform and dense ceramic coating, prevent the intrusion of corrosive substances, and improve the high temperature corrosion resistance of the coating.

[0086] Any matters not described in the present invention are applicable to the prior art.

Claims

1. A thermal barrier coating resistant to marine salt spray corrosion, characterized in that: include: A substrate (1), a bonding layer (2) and a ceramic interlocking layer (3); The substrate (1), the bonding layer (2) and the ceramic interlocking layer (3) are arranged in sequence from bottom to top; The ceramic interlocking layer (3) comprises a transition ceramic layer (301) and a fiber toughening layer (302); a plurality of grooves are evenly arranged on a side of the transition ceramic layer (301) away from the bonding layer (2); protrusions corresponding to the grooves are arranged on a side of the fiber toughening layer (302) in contact with the transition ceramic layer (301); and the transition ceramic layer (301) and the fiber toughening layer (302) are combined into a layered structure through the grooves and the protrusions.

2. The thermal barrier coating for resisting marine salt spray corrosion according to claim 1, characterized in that: The particle sizes in the bonding layer (2), transition ceramic layer (301) and fiber toughening layer (302) are divided into three levels, wherein: The bonding layer (2) is a large particle material with a particle diameter of 300-1000nm; The transition ceramic layer (301) is a micron-sized particle material, and the particle diameter is 200-300nm; The fiber toughening layer (302) is a nano-scale particle material, and the particle diameter is 1-10 nm.

3. The thermal barrier coating resistant to marine salt spray corrosion according to claim 2, characterized in that: The particle size of the bonding layer (2) is controlled by the particle size of the pore-forming agent and the bonding layer material, wherein: The pore-forming agent includes one of polyester powder, polystyrene powder or high-density polyethylene powder.

4. The thermal barrier coating for resisting marine salt spray corrosion according to claim 1, characterized in that: The protrusions are hemispherical protrusions with a sawtooth-shaped cross section, and the diameter of the protrusion structure is 10-40 μm.

5. The thermal barrier coating for resisting marine salt spray corrosion according to claim 1, characterized in that: The base material of the base (1) is a high-temperature nickel-based alloy; the bonding layer material of the bonding layer (2) is a modified NiAl alloy doped with 0.05 at% Hf element.

6. The thermal barrier coating resistant to marine salt spray corrosion according to claim 1, characterized in that: The transition ceramic layer material in the transition ceramic layer (301) is modified YSZ doped with 0.05at%-0.1at% Dy; the toughening layer material in the fiber toughening layer (302) is YSZ doped with SiC fibers, and the mass proportion of SiC fibers in the fiber toughening layer composite material is 10%-30%.

7. A method for preparing a thermal barrier coating resistant to marine salt spray corrosion according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step S1: After preheating the substrate (1), a bonding layer material is sprayed onto the surface of the substrate (1) using a spray gun by a laser cladding method to obtain a bonding layer (2) with a thickness of 100-150 μm; Step S2: Based on step S1, the bonding layer (2) is preheated again, and a transition ceramic layer (301) is immediately deposited on the surface of the bonding layer (2) by laser cladding to obtain a transition ceramic layer (301) with a bonding layer thickness of 200-300 μm; Step S3: Based on step S2, further preheating is performed, and a fiber toughening layer (302) is immediately deposited by electrophoretic deposition to obtain a fiber toughening layer (302) with a thickness of 100-200 μm.

8. The method for preparing a thermal barrier coating resistant to marine salt spray corrosion according to claim 7, characterized in that: The preheating temperature in steps S1 and S3 is 280-300° C., and the preheating time is 15-30 minutes; the preheating temperature in step S2 is 800-850° C., and the preheating time is 15-20 minutes.

9. The method for preparing a thermal barrier coating resistant to marine salt spray corrosion according to claim 7, characterized in that: In step S3, when using electrophoretic deposition, the high-temperature nickel-based alloy of the substrate (1) is used as the positive electrode, and graphite is used as the negative electrode and placed in the suspension, the electrode spacing is 20-100 mm, the deposition voltage is 20-40 V, the deposition time is 2-10 min, and the post-deposition heat treatment temperature is 80-120° C., and the heat treatment time is 4-10 h.

10. The method for preparing a thermal barrier coating resistant to marine salt spray corrosion according to claim 7, characterized in that: At the rear end of the laser cladding spraying in step S2, the spraying device is changed so that the micron particles on the top of the transition ceramic layer (301) are accumulated to present a groove matching the protrusion.

Citation Information

Cited By

  • Heat dissipation coating structure of turbine blade of gas turbine and coating forming method

    CN120006291A

  • Marine high-temperature corrosion environment resistant metal protective coating and preparation method thereof

    CN120425291A